(untitled) (Fiep Bulletin - online, 2014)
The present paper publishes partial results of a study that aims to construct knowledge on School Games and on the understanding of the meaning of the experience for students who participate in them. The context studied is the Municipal School Games of the Education Network of the Metropolitan Region of the City of Porto Alegre, Brazil. The Games, held yearly, are based on the principles and on the concept of Educational Sports. The Games provide the opportunity for the participation of public and private Education Network students aged between 11 and 17 in several sports modalities. The research is devised based on the theoretical and methodological frameworks of the qualitative research and had as its main investigation tools document analysis and semistructured interviews. Study participants were six students of two schools and one Physical Education teacher. The criteria used to choose the school units are related to the number of students and the diversity of modalities registered. Participants were indicated by the directive staffs of schools. The main results of the study show disagreement between the principles and the guidelines of the Games and the pedagogical practice of Physical Education teachers. Students integrate teams by means of selective processes, which enables that the same student participates in different modalities and categories. The School Games calendar defines the planning of school Physical Education, denying students from experiencing different cultures of movement. However, although teachers show attitudes that contradict the principles of Educational Sports, students point socialization and pleasure in playing as justifications and motivations to their participation in this event.